Maintenance of plasmids pBR322 and pUC8 in nonculturable Escherichia coli in the marine environment. - Byrd, J J (1990)
Maintenance of plasmids pBR322 and pUC8 in Escherichia coli that was nonculturable after exposure to seawater was studied. E. coli JM83 and JM101, which contained plasmids pBR322 and pUC8, respectively, were placed in sterile artificial seawater for 21 days. Culturability was determined by plating on both nonselective and selective agar, and plasmid maintenance was monitored by direct isolation of plasmid nucleic acid from bacteria collected on Sterivex filters. E. coli JM83 became nonculturable after incubation for 6 days in seawater yet maintained plasmid pBR322 for the entire period of the study, i.e., 21 days. E. coli JM101 was nonculturable after incubation in seawater for 21 days and also maintained plasmid pUC8 throughout the duration of the microcosm experiment. Direct counts of bacterial cells did not change significantly during exposure to seawater, even though plate counts yielded no viable (i.e., platable) cells. We concluded that E. coli cells are capable of maintaining high-copy-number plasmids, even when no longer culturable, after exposure to the estuarine or marine environment.